INVESTMENT SUPPORT FOR THE DEVELOPMENT OF THE FORESTRY OF UKRAINE IN THE CONTEXT IMPROVING THE COUNTRY FOREST RESOURCE POTENTIAL - Hmyria Viktoriia Petrivna; Polishchuk Valentin Vasilevich; Kozachenko Irina Vladimirovna; Sovgira Svetlana Vasilyevna (Scientific Journal of Pedagogy and Economics, 2019)
The article presents the results of studies that characterize the forest industry of Ukraine as one of the components of the national economy. In turn, the structural elements of the forest sector are: forest chemistry, wood processing, pulp and paper industry. Forest enterprises are independent economic entities in the field of forestry and hunting. These problems predetermine the need for a study of new approaches to the development of investment support principles for the Ukrainian forest industry in the context of increasing the country's forest resource potential. Consideration of investment support of the forestry, analyze the causes, factors and threats associated with a shortage of investment resources in the forest industry and develop proposals for the prospects of investment activity in the direction of using, protecting and recreating the forest resource potential of the region are the purpose of the study. One of the most important conditions for sustainable development at the state level, as well as for individual enterprises, is the maximization of the innovation component of investment support. Obviously, in the conditions of reforming the forestry of Ukraine on the principles of sustainable development the need for an appropriate level of investment support for technological and technical transformation of the forest industry is even more acute. At present, Ukraine cannot meet domestic needs for wood and ensure ecological balance, therefore, studying the potential of forestry and its impact on the country's economy is relevant. In spite of this, a big problem is that after the reorganization of collective farms into agro formation a significant part of the forest was assigned to reserve lands and was left without protection and supervision, that is, the timber potential in these forests is not used. Almost half of the forests of Ukraine are artificially created which need enhanced supervision. On this basis, it is recommended to use in reasonable proportions both the ecological and economic value of forests, ensure reforestation, increase the forest area and prevent the reduction of timber stocks in the forest policy in Ukraine.